Covid-19 prevention by adopting a healthy daily lifestyle - Mahajan, Monalisa (International Journal Of Community Medicine And Public Health, 2020)
The corona virus disease caused by novel coronavirus SARAS-Cov2 is a public health emergency of international concern. Numerous measures have been implemented in many countries to reduce the person to person virus transmission as well as the outbreak. The specific focus of preventive measures is more on the susceptible population of children, healthcare providers, and older people. Many of the people practice safety measures without proper knowledge as to whether these measures are sufficient or not to prevent the spread of the virus As of this time there has no effective pharmaceutical treatment, there should be adopt a way of prevention that is much helpful than cure.